Strong Convergence of New Two-Step Viscosity Iterative Approximation Methods for Set-Valued Nonexpansive Mappings in CAT(0) Spaces. (2nd July 2018) - Xiong, Ting-jian; Lan, Heng-you
Abstract : This paper is for the purpose of introducing and studying a class of new two-step viscosity iteration approximation methods for finding fixed points of set-valued nonexpansive mappings inC A T ( 0 ) spaces. By means of some properties and characteristic toC A T ( 0 ) space and using Cauchy-Schwarz inequality and Xu's inequality, strong convergence theorems of the new two-step viscosity iterative process for set-valued nonexpansive and contraction operators in completeC A T ( 0 ) spaces are provided. The results of this paper improve and extend the corresponding main theorems in the literature.